Food Insecurity, a Determinant of Obesity? - an Analysis from a Population-Based Survey in the Paris Metropolitan Area, 2010 - Martin-Fernandez, Judith (Obes Facts, 2014)
OBJECTIVE: The relationship between food insecurity and obesity is discussed in the literature. The objective of this study was to determine whether food insecurity and obesity were associated in the Paris metropolitan area. METHODS: We used data from third wave of the Health, Inequalities and Social Ruptures (SIRS) cohort study, a longitudinal population-based, representative health and socioepidemiological survey of the general population in the Paris metropolitan area. The participants' BMI (calculated using self-reported height and weight) was analyzed as a continuous variable, and a dichotomous variable (BMI < 30 kg/m(2)/BMI ≥ 30 kg/m(2)) was constructed. Food insecurity was estimated using the Household Food Security Scale Module (HFSSM) and was treated as a trichotomous variable (food security / low food security / very low food security). Multilevel models were estimated for men and women separately. RESULTS: Obesity (BMI ≥ 30 kg/m(2)) prevalence was 10.2%. The determinant of obesity differs according to gender. After adjustment for age, income and the sociooccupational group, very low food security was associated with obesity in women (OR = 2.01, 95%CI 1.05-3.82), and women with very low food security had a higher BMI (Coef. = 1.78, 95% CI 0.24-3.31). This association, however, was not significant for men (OR = 1.84, 95%CI 0.64-5.30). CONCLUSION: In times of economic crisis, it is increasingly essential to explore and understand the pathway through which very low food security is linked to obesity.